Linear-response Description of the Series Resistance of Large-area Silicon Solar Cells: Resolving the Difference between Dark and Illuminated Behavior. (August 2016) - Wagner, Jan-Martin; Schütt, Andreas; Carstensen, Jürgen; Adelung, Rainer
Abstract: Directly from luminescence images it can be shown that, for constant average injection (lumped dark current) and for not-too-large lateral voltage differences, besides the sign, the current flow direction doesn't play any role for the voltages present, so the series resistances in the dark and under illumination are the same. This fits to the results of a linear-response based series resistance description, treating lateral voltage differences on large-area silicon solar cells in linear order in the series resistance as deviation from the case of zero resistance. In this approach it is found that for constant lumped dark current, emitter and grid of a large-area solar cell can be described as a passive network. Therefore, no difference occurs in the voltage distribution caused by inward and outward currents except for the sign. This contradicts several literature works reporting a smaller lumped series resistance of silicon solar cells in the dark than under illumination. However, we show that this contradiction is just a result of the series resistance definition applied in the respective works or that it can be the result of unsuitable measurement conditions. In a numerical modeling of a large-area silicon solar cell as a 1D distributed structure, using exactly the same parameters as Araújo et al . [IEEE-TED 33 (3), 391–401 (1986)] but calculating the lumped series resistance from the integrated Joule losses, we obtain completely different results than Araújo et al .: Under short-circuit condition, the series resistance stays constant, and there is no difference between the open-circuit and dark series resistance; the latter show the same dependence on the diode current density.